Association between Obesity and Metabolic Derangements in Children at Kanti Children’s Hospital, Nepal: A Retrospective Study - Yadav, Anupama Kumari; Karki, Subhana Thapa; Agrawal, Sumit (Journal of College of Medical Sciences-Nepal, 2025)
Background Childhood obesity is rising globally and is now an emerging concern in developing countries like Nepal, where both undernutrition and overnutrition coexist. Childhood obesity is a strong predictor of adult obesity and is associated with increased risk of metabolic and cardiovascular complications. Early detection and management are therefore essential. Body Mass Index (BMI) remains the most feasible tool in clinical practice to diagnose obesity. The objective of this study is to assess the association of BMI with biochemical and radiological parameters (TSH, cholesterol, triglycerides, HDL, LDL, vitamin D, calcium, and liver ultrasonography) in children with obesity. Methods A retrospective study from records of children visiting in Endocrine OPD at Kanti Children’s Hospital from August 2021 to August 2022 with chief complain of increase in weight were included in this study. Association of BMI with level of TSH, cholesterol, triglyceride, HDL, LDL, vitamin D, calcium and ultrasonographic changes in liver were observed. Results After taking height and weight, BMI was calculated and its association with TSH, cholesterol, triglyceride, HDL, LDL, vitamin D, calcium level and ultrasonographic changes in liver were seen. There was significant association between BMI and hypercholesterolemia, hypertriglyceridemia and fatty changes in liver. However, HDL level was not found to be protective. No association between BMI and TSH, level of LDL, vitamin D and calcium were found. Conclusions Since, childhood obesity is significantly associated with dyslipidemia and fatty liver disease, early identification and lifestyle-based interventions are critical to prevent long-term morbidity.